2021
DOI: 10.1111/1467-6427.12340
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy of multiple family therapy in helping Hong Kong Chinese parents recover from depression

Abstract: This paper reports on the results of a clinical study that assessed the treatment efficacy of an adapted model of multiple family therapy (MFT) in helping Hong Kong Chinese parents recovering from depression. A total of sixty-one depressed parents were assigned to either the control group (CG) or the experimental group (EG) on the basis of their motivation and commitment to the MFT programme. Data were collected using standardised measures in the pre-treatment phase (T1), in the post-treatment phase (T2) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In view of the existing knowledge gap, our clinical team and a team of community‐based mental health social workers from the New Life Psychiatric Rehabilitation Association (“the agency”) launched a clinical research project to offer the MFT, a family‐based intervention for Hong Kong Chinese parents in recovery from depression, as a treatment option and assess the efficacy of the MFT for these families. Our study (Ma et al, 2021) showed that after attending the MFT, the psychological distress of the depressed parents in the experimental group (EG) was significantly reduced, and such reduction in symptoms was sustained at the three‐month follow‐up. Compared to the poorly educated depressed parents, highly educated depressed parents benefited more from the MFT.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In view of the existing knowledge gap, our clinical team and a team of community‐based mental health social workers from the New Life Psychiatric Rehabilitation Association (“the agency”) launched a clinical research project to offer the MFT, a family‐based intervention for Hong Kong Chinese parents in recovery from depression, as a treatment option and assess the efficacy of the MFT for these families. Our study (Ma et al, 2021) showed that after attending the MFT, the psychological distress of the depressed parents in the experimental group (EG) was significantly reduced, and such reduction in symptoms was sustained at the three‐month follow‐up. Compared to the poorly educated depressed parents, highly educated depressed parents benefited more from the MFT.…”
Section: Introductionmentioning
confidence: 69%
“…At the baseline (T1), compared to the CG children, the EG children had more behavioral problems, which may possibly be explained by the fact that the EG depressed parents’ psychological distress levels were higher than those of the CG depressed parents (Ma et al, 2021). The symptoms of depression and anxiety in these depressed parents were more pronounced for depressed mothers with low household incomes and those who had been born outside Hong Kong (Xia & Ma, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five trials (17%), of which three included children and their relatives and two included adults and their relatives, had a main focus on mood problems. MFT was associated with improvements in mental health, including mood severity, emotional health, and psychological distress (Fristad et al, 2009; Lemmens et al, 2009; Ma et al, 2021). Lemmens et al (2009) reported a decrease in the number of study participants using antidepressant medication.…”
Section: Resultsmentioning
confidence: 99%